Evaluación de la incidencia de los daños causados por las hormigas cortadoras en plantación de Gmelina arborea ROXB (MELINA) - Moscoso Moreira, Jean Carlos (2021)
The attack of this kind of pest (ants) in the Gmelina arborea plantations manages to affect its development, which reduces its uptake of photosynthesis and thus affects the quality and quantity of the wood harvest; the objective of this project was to evaluate the damage caused by cutter ants in melina. This research was developed in a plantation belonging to the Manobanda group, located in the Quevedo canton, Los Ríos province, during the months of January and February 2021. With the help of so-called "fall" traps located around the entire plantation, it was possible to capture different species of insects, which once identified revealed that cutter ants were the ones that were recorded in greater numbers than the other species. The total of species found were 8, with Atta Cephalotes being the most abundant species; By means of the Shannon and Simpson index, diversity and abundance were determined, respectively. By estimating the incidence of defoliation based on a scale of 0 to 100%, an inventory was carried out in two plots of 500 m2 each, taking a model tree as a reference. The highest percentage of defoliation damage was observed in the second plot, because it is located closer to the main anthill. Keywords: incidence, damage, ant, Atta, abundance.